2010
DOI: 10.1038/onc.2010.254
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between leukemia-associated proteins MOZ and MLL regulates HOX gene expression in human cord blood CD34+ cells

Abstract: MOZ and MLL, encoding a histone acetyltransferase (HAT) and a histone methyltransferase, respectively, are targets for recurrent chromosomal translocations found in acute myeloblastic or lymphoblastic leukemia. In MOZ (MOnocytic leukemia Zinc-finger protein)/CBP-or mixed lineage leukemia (MLL)-rearranged leukemias, abnormal levels of HOX transcription factors have been found to be critical for leukemogenesis. We show that MOZ and MLL cooperate to regulate these key genes in human cord blood CD34 þ cells. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 65 publications
1
47
0
Order By: Relevance
“…7C). Supportive of these findings, another study showed that MOZ and MLL, an H3K4me2/3 HMT complex, interact, colocalize, and functionally cooperate on multiple HOX promoters (Paggetti et al 2010), highlighting the relationships between MOZ and the modifications of H3K4me3 and H3K14ac.…”
Section: Combinatorial Action Of Epigenetic Readers In the Moz Complexmentioning
confidence: 72%
See 1 more Smart Citation
“…7C). Supportive of these findings, another study showed that MOZ and MLL, an H3K4me2/3 HMT complex, interact, colocalize, and functionally cooperate on multiple HOX promoters (Paggetti et al 2010), highlighting the relationships between MOZ and the modifications of H3K4me3 and H3K14ac.…”
Section: Combinatorial Action Of Epigenetic Readers In the Moz Complexmentioning
confidence: 72%
“…Moreover, one recent study in HEK293T and CD44 + cells has demonstrated the binding of MOZ to the HOXA9 gene promoter (Paggetti et al 2010). In light of our findings that the tandem PHD finger of MOZ could interact with the histone H3 tail, an interesting question emerges as to whether this binding contributes to a gene-specific targeting.…”
Section: Phd12 Contributes To the Localization Of Moz On The Hoxa9 Prmentioning
confidence: 99%
“…S10) (46). Interestingly, MOZ itself is also able to bind H3K4me3 (47). The presence of multiple histone binding domains in a single complex raises the following questions.…”
Section: Discussionmentioning
confidence: 99%
“…MLL1 interacts physically and/or genetically with p300/CBP, MOF, and MOZ histone acetyltransferases (Dou et al, 2005;Ernst et al, 2001;Paggetti et al, 2010). Although the CBP/p300-mediated H3K27Ac and MOZ-mediated H3K9Ac modifications were stable throughout the time course ( Figures S4E, S5A, and S5B), H4K16Ac was rapidly reduced around the TSS of MLL1 target genes in Mll1 Δ/Δ cells ( Figure 5A) as was MOF itself ( Figure 5B).…”
Section: H4k16 Acetylation At Mll1 Targets Is Lost In Parallel With Tmentioning
confidence: 99%